Butterfly hug therapy on reducing anxiety levels and stabilization hemodynamics in patient digital subtraction angiography - Astuti, Anis Wiji; Rosyid, Fahrun Nur; Subrata, Sumarno Adi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Background: Digital subtraction angiography can affect anxiety in patients so that it can worsen the patient's condition during catheterization, such as increased heart rate and breathing. One of the efforts to reduce anxiety that can improve hemodynamics is butterfly hug therapy. However, its effectiveness in reducing hemodynamic anxiety needs to be further investigated. Purpose: To evaluate butterfly hug therapy's effectiveness on anxiety and hemodynamics before digital subtraction angiography. Methods: This is a quasi-experiment study with a pretest-posttest control group design. Fifty-two respondents were selected using purposive sampling. A total of 26 respondents were given butterfly hug therapy, and 26 others were given standard therapy. The study implemented the Zung Self Rating Anxiety Scale Questionnaire and observation sheet. This research analysis uses the Independent T-test and Wilcoxon Test. Results: The anxiety level of the experimental group was lower than that of the control group (46.73 ± 2.08 vs. 53.84 ± 1.74; p<0.05). In hemodynamic stability (pulse, respiratory, and blood pressure) was stability than the control group (80.69 ± 2.44 vs. 89.11 ± 2.39; 20.65 ± 0.39 vs. 21.0 ± 0.53; 104.7 ± 1.46 vs. 109.5 ± 1.82; p <0.05). Conclusion: Butterfly hug therapy is effective in reducing anxiety and stabilizing hemodynamics among patients undergoing digital subtraction angiography.